Analysis of factors influencing the job satisfaction of medical staff in tertiary public hospitals, China: A cross-sectional study - Shi, Xiang; Xiong, Dekai; Zhang, Xingmin; Han, Miaomiao; Liu, Liu; Wang, Jinian (Frontiers in Psychology, 2023)
Since the outbreak of COVID-19, China has entered a normalization phase. However, medical staff continue to face physical and mental stress. We aimed to investigate the job satisfaction of medical staff and its associated factors. Specifically, we conducted a cross-sectional study of data collected from medical staff (e.g., doctors, nurses, medical technicians, and other administrative staff) from 13 tertiary care institutions in Anhui Province, China using questionnaires. A total of 2300 questionnaires were distributed, and after excluding those that did not meet the criteria, 2258 questionnaires were included in the study. Based on the Minnesota Satisfaction Scale and AskFormQ38 Satisfaction Scale, the following 7 dimensions were obtained with appropriate adjustments: compensation and benefits, job content, career development, organizational management, work environment, interpersonal relationship, and hospital culture. Binary logistics regression was used to assess the factors influencing the job satisfaction of medical staff in Anhui Province under the normalization of epidemic prevention and airing. Job satisfaction among the medical staff was associated with being aged 40–49 years (odds ratio [OR]=2.416) or >50 years (OR=2.440), having an education level above an undergraduate degree (OR=1.857), holding a position other than a doctor (i.e. nurse [OR=3.696] or “other” [OR=2.423]), having a higher income (OR=1.369), and having fewer monthly overtime shifts (OR=0.735-0.543). To improve medical workers’ job satisfaction, administrators should seek to enhance their remuneration, reduce work pressure, and meet their reasonable needs.